Representasi Femininitas Baru dalam Iklan MS Glow X Ayu Dewi - Shintiya Gebi Fitriya (Jurnal Ilmu Komunikasi, 2022)
The increasing number of users of beauty products has finally forced manufacturers to increase their production. Beauty products have increased very rapidly. One beauty product that currently has a lot of fans is MS Glow. The variety of beauty products circulating in society makes business competition even higher. In order to continue to exist in the market, MS Glow is increasingly aggressively attracting consumers. One way to attract the attention of consumers is with advertising. an MS Glow advertisement that was uploaded on the MS Glow Beauty YouTube account on April 4, 2022 entitled “MS Glow x Ayu Dewi. This advertisement was starred by one of the artists in Indonesia, namely Ayu Dewi. The advertisement tells the story of a housewife who is very happy with all the household activities she does. Being a versatile housewife is a dream for her. However, the ad does not only present herself as a housewife. She also appears as a career woman who does several jobs. From what the researchers observed, the ad contained signs that presented a new representation of femininity. This study uses Roland Barthes' semiotic analysis. And the results of this study show that the representation of new femininity is displayed by selecting the colors used in each scene, starting from the selection of sentences in the narration used, the selection of highlighted colors, the selection of properties such as clothing, make-up, cooking utensils.